2020
DOI: 10.1111/jcmm.15041
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of higenamine combined with [6]‐gingerol on chronic heart failure induced by doxorubicin via ameliorating mitochondrial function

Abstract: Higenamine (HG) is a natural benzylisoquinoline alkaloid isolated from Aconitum with positive inotropic and chronotropic effects. This study aimed to investigate the possible cardioprotective effects of HG combined with [6]-gingerol (HG/[6]-GR) against DOXinduced chronic heart failure (CHF) by comprehensive approaches. DOX-induced cardiotoxicity model in rats and H9c2 cells was established. Therapeutic effects of HG/[6]-GR on haemodynamics, serum indices and histopathology of cardiac tissue were analysed. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…However, the cardiotoxic effects of DOX limit its use in cancer patients with irreversible degenerative cardiomyopathy and heart failure. More than half of the elderly patients and children who survive lymphoma and other cancers, respectively, show a high risk of cardiotoxicity after DOX treatment [ 7 ]. Therefore, it is essential to study DOX-induced myocardial injury to increase survival rates and improve the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cardiotoxic effects of DOX limit its use in cancer patients with irreversible degenerative cardiomyopathy and heart failure. More than half of the elderly patients and children who survive lymphoma and other cancers, respectively, show a high risk of cardiotoxicity after DOX treatment [ 7 ]. Therefore, it is essential to study DOX-induced myocardial injury to increase survival rates and improve the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters were comprehensively detected in the current study. Our previous study has shown that HG in combination with [6]-GR can substantially increase the CPT-1 level decreased by DOX, which can relieve cardiomyocyte injury induced by DOX via regulating fatty acid metabolism in the TCA cycle based on cell metabonomics [20]. In the present study, serum metabonomics coupled with integrative pharmacology has further improved our understanding of the therapy of DOX induced CHF with HG/[6]-GR from several pivotal aspects.…”
Section: Discussionmentioning
confidence: 67%
“…All rats were intraperitoneally injected with corresponding drugs once a day for seven consecutive days. It should be noted that CHF rats intraperitoneally injected with 5 mg/kg/d HG and [6]-GR showed a good therapeutic effect in our previous study [20]. Hemodynamic indices were assessed after the nal injection.…”
Section: Animal Handlingmentioning
confidence: 94%
“…The results showed that HG/ Our previous study has shown that HG in combination with [6]-GR can substantially increase the CPT-1 level decreased by DOX, which can relieve cardiomyocyte injury induced by DOX via regulating fatty acid metabolism in the TCA cycle based on cell metabolomics. [20] In the present study, serum metabolomics coupled with integrative pharmacology has further improved our understanding of the therapy of DOX induced CHF with HG/[6]-GR from several pivotal aspects.…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that CHF rats intraperitoneally injected with 5 mg/kg/d HG and [6]-GR showed a good therapeutic effect in our previous study. [20] Hemodynamic indices were assessed after the nal injection. All animals were sacri ced to collect serum samples and cardiac tissues for HE staining, TUNEL staining, and metabolomic analysis.…”
Section: Animal Handlingmentioning
confidence: 99%